C5-substituted pyrido[2, 3-d]pyrimidin-7-ones as highly specific kinase inhibitors targeting the clinical resistance-related EGFRT790M mutant1. Issue 9 (2nd September 2015) - Xu, Tianfeng; Peng, Ting; Ren, Xiaomei; Zhang, Lianwen; Yu, Lei; Luo, Jinfeng; Zhang, Zhang; Tu, Zhengchao; Tong, Linjiang; Huang, Zhaoru; Lu, Xiaoyun; Geng, Meiyu; et al.
<x xml:space="preserve">Abstract</x> C5-substituted pyrido[2, 3-d]pyrimidin-7-ones were discovered as highly potent and specific inhibitors targeting the clinical resistance-related EGFRL858R/T790M mutant.